2018
DOI: 10.3382/ps/pex408
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin attenuates heat-stress-induced oxidant damage by simultaneous activation of GSH-related antioxidant enzymes and Nrf2-mediated phase II detoxifying enzyme systems in broiler chickens

Abstract: The object of this study was to investigate the effect of curcumin on modulating the glutathione (GSH)-related antioxidant enzymes and antioxidant responses via NF-E2-related factor 2 (Nrf2) signaling pathway in heat-stressed broiler chickens. A total of 400 one-day-old male Arbor Acres broiler chicks was reared in an environmentally controlled room. At 21 d, broiler chicks were divided into 5 treatment groups and were fed one of 4 diets under 2 temperature conditions: 22°C + a basal diet (CON treatment); 34°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 39 publications
7
69
0
Order By: Relevance
“…Glutathione antioxidant system plays a pivotal role in cellular defense against ROS, GSH-Px function either directly or indirectly as antioxidants, and GSH plays an important role in scavenging reactive oxygen species [47]. It has been reported that dietary chitosan supplementation could enhance the serum SOD, CAT, and GSH-Px of diquat challenged weaning pigs [48]. In addition, dietary chitosan supplementation can prevent lipid peroxidation induced by LPS and retain GSH and CAT activity [42].…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione antioxidant system plays a pivotal role in cellular defense against ROS, GSH-Px function either directly or indirectly as antioxidants, and GSH plays an important role in scavenging reactive oxygen species [47]. It has been reported that dietary chitosan supplementation could enhance the serum SOD, CAT, and GSH-Px of diquat challenged weaning pigs [48]. In addition, dietary chitosan supplementation can prevent lipid peroxidation induced by LPS and retain GSH and CAT activity [42].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that various feed supplements, such as curcumin, lycopene, and some microelement can alleviate oxidative damage caused by chronic heat stress in broilers by modulating the expression of Nrf2 ( Sahin et al., 2016 , 2017 ; Zhang et al., 2018 ). However, under the condition of acute heat stress, limited information is available about the antioxidant potential and related regulatory mechanism of broilers.…”
Section: Introductionmentioning
confidence: 91%
“…The protective effects of other phytochemicals against Nrf2-related AO enzyme changes due to the presence of HS were also reported. For example, curcumin supplementation (50-200 mg/kg) was shown to improve AO defences of HS-exposed broilers, as evidenced by increasing the GSH content and GSH-related enzyme activities and inducing the expression of Nrf2 and Nrf2-mediated phase II detoxifying enzyme genes [259]. Interestingly, birds in the HS group showed increased MDA, protein carbonyl (PC), 8-hydroxydeoxyguanosine (8-OHdG) and some apoptosis markers, including caspase-3 and caspase-9 mRNA levels and activity.…”
Section: Heat Stressmentioning
confidence: 99%